Synthesis and characterization of SSM@NiO/TiO2 p-n junction catalyst for bisphenol a degradation. (December 2022) - Kim, Nahee; Ali, Mumtaz; Anwer, Hassan; Park, Jae-Woo; Irfan, Iqra
Abstract: Photocatalyst immobilization on support materials is essential for large-scale applications. Here, we describe growth of a p-n junction catalyst (NiO/TiO2 ) on a stainless-steel mesh (SSM) support using a facile hydrothermal method. The morphological superiority of the composite over previously reported NiO/TiO2 catalysts was probed using scanning and transmission electron microscopy. Flower petal–like NiO grew uniformly on SSM, which was evenly covered by TiO2 nanoparticles. Theoretical and experimental X-ray diffraction patterns were compared to analyze the development of the composite during various stages of synthesis. The photocatalytic activity of a powdered catalyst and SSM@catalyst was compared by measuring bisphenol A (BPA) degradation. SSM@NiO/TiO2 achieved the highest rate of BPA degradation, removing 96% of the BPA in 120 min. Scavenging experiments were used to investigate the charge separation and degradation mechanism. SSM@NiO/TiO2 showed excellent reusability potential, achieving and sustaining 91% BPA removal after 10 rounds of cyclic degradation. Reusability performance, composite resilience, apparent quantum yields, and figures of merit suggest that SSM@NiO/TiO2 has excellent utility for practical applications. Graphical abstract: Image 1 Highlights: NiO/TiO2 p-n junction catalyst was grown on stainless-steel mesh (SSM). SSM@NiO/TiO2 exhibited better photocatalytic performance than powder-type catalyst. Scavenging experiments verified the p-n junction supported charge separation. Only 5% reduction in performance occurred after 10-rounds of BPA degradation.